The Open Map - Başak Uçar; Pelin Yoncacı Arslan (Footprint)
Maps are preeminent ways of collecting, organising, verifying, historicising, and even mystifying territorial knowledge. They embrace a multiplicity of readings and readers, and mediate between the visible and the invisible. In constant re-definition, maps transform and maximise themselves by connecting different layers of information and initiating uninterrupted performances. Without delineating a fixed meaning, maps respond to the city’s openness via diversity, incompleteness, and unpredictability. New developments in computer science and information technologies have turned maps into grittier models that define the new granular front of the open map. This article studies open maps in terms of participation and multiplicity, part and whole relationships, and resolution vis-à-vis Jasper Johns’s paintings, Buckminster Fuller’s Dymaxion Map and the World Game, and the MIT’s Real-time Rome project.